HLA antibody screening in kidney transplantation: current guidelines - Wettstein, Daniel; Opelz, Gerhard; Süsal, Caner (Langenbeck's archives of surgery, 2014)
In organ transplantation, the introduction of the solid phase immunoassay technology radically changed the practice of antibody monitoring against human leukocyte antigens (HLA).